Aspek Hukum Upaya Pelestarian Situs Tamansari Yogyakarta sebagai Salah Satu Warisan Budaya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The research aims to study the regulatory of Tamansari (Water Castle) as one of the cultural heritages which is threatened with extinction, and to study the efforts to preserve it. The research belongs to a descriptive analytical research. It uses primary and secondary data. The research results show that the Tamansari is not regulated in the national legislation itself Meanwhile, the Tamansari preservation is committed by restoration, improvement of tourism, and socialization of the culture preserve regulation.